Synthesis of SZR framework molecular sieves

JP7634566B2Active Publication Date: 2025-02-21CHEVRON USA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022574516
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-03
Filing Date
2021-05-18
Publication Date
2025-02-21
Estimated Expiration
2041-05-18

Smart Images

  • Figure 0007634566000009
    Figure 0007634566000009
  • Figure 0007634566000010
    Figure 0007634566000010
  • Figure 0007634566000011
    Figure 0007634566000011
Patent Text Reader

Abstract

A method for synthesizing SZR framework molecular sieves is provided using 1,2,3-trimethylimidazolium cation as a structure directing agent and alumina-coated silica as a combined source of silicon and aluminum.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 033,943, filed June 3, 2020.

[0002] Field The present disclosure relates to a method for preparing SZR framework-based molecular sieves. [Background technology]

[0003] background Molecular sieves are a commercially important class of materials with unique chemical compositions and distinct crystal structures with well-defined pore structures revealed by distinctive X-ray diffraction (XRD) patterns. The crystal structures reveal the voids and pores characteristic of a particular type of molecular sieve.

[0004] Crystalline microporous materials are classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on Zeolite Nomenclature. Framework zeolites and other crystalline microporous crystal materials with established structures are assigned three-letter codes according to this classification and are published in the "Atlas of Zeolite Framework Types" (Sixth Revised Edition, Elsevier, 2007).

[0005] One known crystalline material with established structure is the material designated as SZR framework type, including most notably SUZ-4. The three-dimensional pore system of SUZ-4 consists of a straight 10-membered ring (MR) pore and two intersecting 8MR zigzag pores. Crystalline SUZ-4 and its conventional preparation using tetraethylammonium cation as a structure directing agent are taught by U.S. Pat. No. 5,118,483. Zeolite SUZ-4 has a needle-like morphology (see, for example, SL Lawton et al., J. Chem. Soc., Chem. Commun. 1993, 894-896 and KG Strohmaier et al., Z.Krystallogr. 2006, 221, 689-698). Zeolites with needle-like morphology are undesirable due to the health concerns associated with them.

[0006] US Pat. No. 10,399,066 discloses aluminosilicate SZR framework-type zeolites JMZ-5 and JMZ-6 having needle-like and needle-aggregate morphologies, respectively, and methods for their preparation.

[0007] In accordance with the present disclosure, it has been discovered that SZR framework molecular sieves, particularly those having improved morphology, can be prepared using 1,2,3-trimethylimidazolium cation as a structure directing agent and alumina-coated silica as a source of silicon and aluminum. Summary of the Invention

[0008] summary In one aspect, a method for synthesizing an SZR framework type molecular sieve is provided, the method comprising: (1) preparing a reaction mixture comprising: (a) alumina-coated silica; (b) a source of an alkali or alkaline earth metal (M); (c) a structure directing agent comprising a 1,2,3-trimethylimidazolium cation (Q); (d) a source of hydroxide ions; and (e) water; and (2) exposing the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve.

[0009] In another aspect, there is provided an SZR framework-based molecular sieve and its as-synthesized morphology that contains 1,2,3-trimethylimidazolium cations within the pores. In relation to the present invention, the following is further disclosed: [1] 1. A method for synthesizing an SZR framework type molecular sieve, comprising the steps of: (1) (a) Alumina-coated silica (b) A source of alkali or alkaline earth metal (M) (c) a structure directing agent containing a 1,2,3-trimethylimidazolium cation (Q) (d) A source of hydroxide ions (e) water preparing a reaction mixture comprising: (2) exposing said reaction mixture to crystallization conditions sufficient to form crystals of said molecular sieve. The method comprising: [2] The reaction mixture has the following composition expressed by molar ratio: [Table 1A] The method according to claim 1, comprising: [3] The reaction mixture has the following composition, expressed in molar ratios: [Table 1B] The method according to claim 1, comprising: [4] The method according to [1], wherein the alkali or alkaline earth metal (M) comprises potassium. [5] The method according to [1], wherein the crystallization conditions include a temperature of 100° C. to 200° C. and a time of 1 to 14 days. [6] A SZR framework-based molecular sieve containing 1,2,3-trimethylimidazolium cations within the pores and its as-synthesized morphology. [7] SiO in the range of 10~80 2 / Al 2 O 3 The molecular sieve according to [6], having a molar ratio of [8] SiO in the range of 15~50 2 / Al 2 O 3 The molecular sieve according to [6], having a molar ratio of [Brief description of the drawings]

[0010] Brief description of the drawings [Figure 1] 1 shows the powder X-ray diffraction (XRD) pattern of the as-synthesized SZR framework molecular sieve product of Example 1.

[0011] [Figure 2A] 1 shows scanning electron microscope (SEM) images of the as-synthesized SZR framework molecular sieve product of Example 1 at various magnifications. [Figure 2B] 1 shows scanning electron microscope (SEM) images of the as-synthesized SZR framework molecular sieve product of Example 1 at various magnifications.

[0012] [Diagram 3] 1 shows a powder XRD pattern of zeolite SUZ-4 prepared according to U.S. Pat. No. 10,399,066.

[0013] [Figure 4A] 1 shows SEM images of zeolite SUZ-4 prepared according to US Pat. No. 10,399,066 at various magnifications. [Figure 4B] 1 shows SEM images of zeolite SUZ-4 prepared according to US Pat. No. 10,399,066 at various magnifications.

[0014] [Diagram 5] 1 shows the powder XRD pattern of the ammonium form SZR framework molecular sieve of Example 4.

[0015] [Figure 6] 1 shows the powder XRD pattern of the ammonium form of SUZ-4 zeolite of Example 5.

[0016] [Figure 7]1 is a graph showing the relationship between conversion or yield and temperature for the hydroconversion of n-decane over a Pd / SZR catalyst.

[0017] [Figure 8] 1 is a graph showing the relationship between C10 monobranched isomer product distribution and conversion rate for n-decane hydroconversion over Pd / SZR catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Detailed Description definition The term "molecular sieve" is used synonymously with the term "microporous crystalline material" or "zeolite."

[0019] The term "framework type" as used herein has the meaning set forth in "Atlas of Zeolite Framework Types" by Ch. Baerlocher, LB McCusker and DH Olson (Elsevier, Sixth Revised Edition, 2007).

[0020] The term "as-synthesized" refers to the molecular sieve in the form after crystallization and prior to removal of the structure-directing agent.

[0021] The term "anhydrous" refers to molecular sieves that are substantially free of both physisorbed and chemisorbed water.

[0022] The term "SiO2 / Al2O3 molar ratio" may be abbreviated as "SAR."

[0023] Synthesis of molecular sieves SZR framework type molecular sieves may be synthesized by (1) preparing a reaction mixture comprising (a) alumina-coated silica, (b) a source of an alkali or alkaline earth metal (M), (c) a structure directing agent comprising a 1,2,3-trimethylimidazolium cation (Q), (d) a source of hydroxide ions, and (e) water, and (2) exposing the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve.

[0024] The reaction mixture was prepared in the ranges shown in Table 1, expressed as molar ratios: [Table 1] where M is an alkali or alkaline earth metal and Q comprises a 1,2,3-trimethylimidazolium cation.

[0025] The alumina-coated silica may be a single type of alumina-coated silica or a mixture of two or more alumina-coated silica materials with different silica to alumina molar ratios. In some embodiments, colloidal aluminosilicate sol-gel is used as the sole or primary source of silicon and aluminum. Alumina-coated silica with various SiO2 / Al2O3 molar ratios (e.g., 35, 80, 100, 127) is available from Nalco (Naperville, Illinois).

[0026] An alkali or alkaline earth metal (M) is typically introduced into the reaction mixture together with a source of hydroxide ions. Examples of such metals include sodium and / or potassium, and also include lithium, rubidium, cesium, magnesium, and calcium. As used herein, the phrase "alkali or alkaline earth metal" does not mean that alkali metals and alkaline earth metals are used in the alternative, but rather that one or more alkali metals can be used alone or in combination with one or more alkaline earth metals, and one or more alkaline earth metals can be used alone or in combination with one or more alkali metals.

[0027] The structure inducer has the following structure (1): [ka] It contains a 1,2,3-trimethylimidazolium cation (Q) represented by the following formula:

[0028] Suitable sources of Q are the hydroxides, chlorides, bromides, and / or other salts of quaternary ammonium compounds.

[0029] The reaction mixture may contain seeds of crystalline material, such as SZR framework molecular sieves from a previous synthesis, desirably in an amount of 0.01 to 10,000 wppm (e.g., 100 to 5,000 wppm) based on the weight of the reaction mixture. Seeding may be beneficial in improving selectivity to SZR and / or shortening the crystallization process.

[0030] It should be noted that the reaction mixture components may be supplied by multiple sources, or two or more reaction components may be provided by a single source. The reaction mixture may be prepared in either a batch or continuous manner.

[0031] Crystallization of the desired molecular sieve from the reaction mixture can be carried out under either static, rotating or stirred conditions in a suitable reaction vessel, such as a polypropylene bottle, or a Teflon-lined or stainless steel autoclave, at a temperature of 100° C. to 200° C. (e.g., 150° C. to 180° C.) for a time sufficient to allow crystallization to occur, e.g., about 1 to 14 days. Crystallization is often carried out under pressure in the autoclave, such that the reaction mixture is exposed to autogenous pressure.

[0032] Once the desired molecular sieve crystals have formed, the solid product may be separated from the reaction mixture by standard mechanical separation techniques such as centrifugation or filtration. The crystals are washed with water and then dried to obtain the as-synthesized molecular sieve crystals. The drying step may be carried out at elevated temperatures (e.g., 75°C to 150°C) for several hours (e.g., 4 to 24 hours). The drying step may be carried out under vacuum or at atmospheric pressure.

[0033] As a result of the crystallization process, the recovered crystalline molecular sieve product contains within its pores at least a portion of the structure-directing agent used during synthesis.

[0034] The as-synthesized molecular sieve may be subjected to heat treatment, ozone treatment, or other treatment to remove some or all of the structure directing agent used in its synthesis. Removal of the structure directing agent may be accomplished by heat treatment (i.e., calcination) in which the as-synthesized molecular sieve is heated in air or in an inert gas at a temperature sufficient to remove some or all of the structure directing agent. Subatmospheric pressure may be used for the heat treatment, but for reasons of convenience, atmospheric pressure is preferred. The heat treatment may be performed at a temperature of at least 370° C. for at least 1 minute, and typically for up to 20 hours (e.g., 1-12 hours). The heat treatment may be performed at a temperature up to 925° C. For example, the heat treatment may be performed in air at a temperature of 400° C. to 600° C. for approximately 1-8 hours.

[0035] Any extraframework metal cations in the molecular sieve may be replaced with other cations according to techniques well known in the art (e.g., by ion exchange). The replacing cations may include metal ions, hydrogen ions, hydrogen precursor ions (e.g., ammonium ions), and combinations thereof.

[0036] The SZR framework molecular sieves of the present invention may be formulated into catalyst compositions by combining them with other materials, such as binders and / or matrix materials which impart additional rigidity or catalytic activity to the finished catalyst. When combined with such components, the relative proportions of SZR framework molecular sieve and matrix may vary considerably, with the SZR framework molecular sieve content ranging from 1 to 90% by weight (e.g., 2 to 80% by weight) of the total composite.

[0037] Characterization of molecular sieves The SZR framework molecular sieves prepared as described herein, in their as-synthesized anhydrous form, have molar ratios in the ranges shown in Table 2: [Table 2] where Q comprises a 1,2,3-trimethylimidazolium cation and M is an alkali or alkaline earth metal.

[0038] example The following illustrative examples are intended to be non-limiting.

[0039] Example 1 Synthesis of SZR-type zeolite 3.8 g of 1N KOH was combined with 0.29 g of 1,2,3-trimethylimidazolium hydroxide (2.16 mmol OH / g), 2.86 g of deionized water, and finally 4.00 g of Nalco alumina-coated silica DVSZN007 (SAR=35, 24.5% solids). The final reaction mixture had the following composition in molar ratios: 1 SiO2: 0.0286 Al2O3: 0.24 KOH: 0.04 Q-OH: 34 H2O

[0040] The mixture was thoroughly stirred, placed in an autoclave, sealed, and heated at 170° C. for 6 days with stirring at 43 rpm. The material was collected by filtration, washed with copious amounts of water, and finally dried in air at 85° C.

[0041] The resulting product was analyzed by powder XRD and SEM. The powder XRD pattern shows that the material is pure SZR zeolite, as shown in Figure 1. SEM images of the product are shown at various magnifications in Figures 2A and 2B. Figures 2A and 2B show that the material does not have the high aspect ratio needle morphology.

[0042] Example 2 (Comparative Example) Synthesis of zeolite SUZ-4 As a comparative example, zeolite SUZ-4 was synthesized according to Example 1 of US Pat. No. 10,399,066 by combining 5.8 g of deionized water with 1.15 g of 45 wt. % KOH, followed by dissolving 0.06 g of aluminum foil. After dissolution, 0.93 g of 35 wt. % tetraethylammonium hydroxide was added, followed by 4.88 g of LUDOX® AS-30 colloidal silica. The mixture was thoroughly homogenized, sealed in an autoclave, and heated with stirring at 150° C. and 43 rpm for 4 days. The material was collected by filtration, washed with copious amounts of water, and finally dried in air at 85° C.

[0043] The resulting product was analyzed by powder XRD and SEM. The powder XRD pattern shows that the material is pure SUZ-4 zeolite, as shown in Figure 3. SEM images of the product are shown at various magnifications in Figures 4A and 4B. Figures 4A and 4B show the material has a high aspect ratio needle morphology.

[0044] Example 3 Calcination of SZR-type zeolite The as-synthesized material from Example 1 was placed in a thin layer in a calcination dish and calcined in air by heating in a muffle furnace at a rate of 1°C / min up to a room temperature of 120°C and holding at 120°C for 2 hours. The temperature was then increased to 540°C at a heating rate of 1°C / min and held at 540°C for 5 hours. The temperature was again increased at 1°C / min to 595°C and held at 595°C for 5 hours. The material was then allowed to cool to room temperature.

[0045] Example 4 Ammonium ion exchange of SZR-type zeolites The potassium form as-synthesized material from Example 3 was converted to the ammonium form by heating in a solution of ammonium nitrate (typically 1 g NH4NO3 / 1 g zeolite in 10 mL H2O at 85° C. for at least 3 hours). The material was then filtered. This was repeated twice for a total of three exchanges. Finally, the material was washed with deionized water until the conductivity of the water was less than 10 μS / cm. The powder XRD pattern of the ammonium exchanged product is shown in FIG. 5.

[0046] The dried product was subjected to micropore volume analysis by BET method using N2 as the adsorbent. The zeolite had a volume of 0.13 cm 3 / g micropore volume.

[0047] The acid site density was characterized using n-propylamine temperature programmed desorption (TPD) with 525 μmol H + / g.

[0048] As determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES) elemental analysis, the product had a SiO2 / Al2O3 molar ratio of 33.6 and a K / Al molar ratio of 0.23, indicating that not all potassium could be removed by ammonium exchange. This amount of non-exchangeable sites is consistent with previous findings. See, for example, D.B. Lukyanov et al. (J. Phys. Chemistry B 1999, 103, 197-202).

[0049] Example 5 (Comparative Example) Calcination of zeolite SUZ-4 The as-synthesized material from Example 2 was calcined in the same manner as described in Example 3.

[0050] Example 6 (Comparative Example) Ammonium ion exchange of zeolite SUZ-4 The potassium form as-synthesized SUZ-4 material from Example 5 was converted to the ammonium form using the method described in Example 4. Figure 6 shows the powder XRD pattern of the ammonium ion-exchanged material.

[0051] Example 7 Palladium Exchange For palladium exchange to 0.5 wt% Pd, 0.8 g of the ammonium form material prepared in Example 4 was combined with 7.44 g of deionized water and 3.48 g of 0.156N NH4OH solution, followed by 0.80 g of palladium solution prepared by combining 0.36 g of tetraamminepalladium(II) nitrate with 21 g of deionized water and 3 g of 0.148N NH4OH solution. The pH was then checked and adjusted, if necessary, by dropwise addition of concentrated ammonium hydroxide until the pH reached a value of 10. After standing at room temperature for 3 days, the pH was checked again and readjusted to 10, if necessary, and allowed to stand for another day. The material was collected by filtration, washed with deionized water, and dried overnight in air at 85°C. The Pd-formed material was calcined in dry air by heating at a ramp of 1 °C / min to 120 °C, holding at 120 °C for 180 min, then heating at a ramp of 1 °C / min to 482 °C and holding at 482 °C for 180 min. Finally, the material was pelletized at 5 kpsi and sieved through a 20-40 mesh sieve.

[0052] Example 8 Conversion of methanol to hydrocarbons in SZR-type zeolites. For methanol to hydrocarbon catalytic testing, the ammonium form material from Example 4 was pelletized at 5 kpsi, crushed, and sieved through a 20-40 mesh sieve. 0.20 g of the dehydration catalyst (diluted 4:1 v / v with alundum), determined by thermogravimetric analysis (TGA) at 600 °C, was placed in the center of a downflow stainless steel tubular reactor in a split tube furnace. The catalytic reaction was carried out at atmospheric pressure. The catalyst was preheated in situ under flowing nitrogen at 400 °C. A feedstock of pure methanol was added to the reactor for 1.3 h with nitrogen flowing at 30 mL / min as carrier gas. -1 The WHSV was fed at a rate of 0.324 mL / h. The reaction products from the product stream exiting the reactor were automatically injected into a working Agilent gas chromatograph equipped with a flame ionization detector and analyzed in situ. The results are shown in Table 3. [Table 3]

[0053] Example 9 Determination of constraint indices for SZR framework zeolites. The ammonium form of the SZR framework molecular sieve of Example 4 was pelletized at 4-5 kpsi, crushed, and sieved through a 20-40 mesh screen. 0.47 g of the dehydration catalyst, as determined by TGA at 600° C., was then loaded into a 3 / 8 inch stainless steel tube with alundum on both sides of the molecular sieve layer. The reactor was heated using a Lindburg furnace. Helium was introduced into the reactor at atmospheric pressure at 10 mL / min. The reactor was heated to approximately 371° C. and a 50 / 50 (w / w) n-hexane and 3-methylpentane feedstock was introduced into the reactor at a rate of 8 μL / min with helium carrier gas at 10 mL / min. The feedstock delivery was by an ISCO pump. Direct sampling to a gas chromatograph (GC) was started 15 minutes after the feedstock was introduced.

[0054] Constraint index values ​​were calculated from the GC data using methods known in the art and were found to be between 2.87 and 3.39 (less than 30% conversion) for flow times of 15 to 225 minutes, which is characteristic of 10-ring molecular sieves.

[0055] Example 10 (Comparative Example) Determination of the constraint index of SUZ-4 zeolite The constraint index values ​​(excluding 2-methylpentane) of the SUZ-4 zeolite of Example 6 were measured in the same manner as described in Example 9 and were found to be between 1.72 and 2.65 (less than 30% conversion) for flow times of 15 to 225 minutes, which is characteristic of a 10-ring molecular sieve.

[0056] Example 11 Hydroconversion of n-decane For catalytic testing, 0.5 g of Pd / SZR catalyst from Example 7 (weight of sample determined to be dehydrated by TGA at 600° C.) was loaded into the center of a 23 inch long by ¼ inch OD stainless steel reactor tube (1200 psig total pressure, 12.5 mL / min downflow hydrogen rate measured at 1 atm and 25° C., and 1 mL / hr downflow liquid feed rate) with alundum loaded upstream of the catalyst for feed preheating. The catalyst was first reduced in flowing hydrogen at 315° C. for 1 hour. The reaction was run from 230° C. to 310° C. Products were analyzed approximately once every 60 minutes by a running capillary GC. Raw data from the GC was collected by an automated data collection / processing system, and hydrocarbon conversion was calculated from the raw data. Conversion is defined as the amount in mol% of n-decane that reacted to produce other products (including iso-C10). The yield of iso-C10 is expressed as the mole percent of products other than n-decane. The yield of cracking products (smaller than C10) is expressed as the mole percent of n-decane converted to cracking products. The results are shown in Figures 7 and 8.

Claims

1. A method for synthesizing an SZR framework type molecular sieve, comprising the steps of: (1) (a) Alumina-coated silica (b) A source of alkali or alkaline earth metal (M) (c) A structure directing agent containing a 1,2,3-trimethylimidazolium cation (Q) (d) a source of hydroxide ions (e) Water preparing a reaction mixture comprising: (2) exposing the reaction mixture to crystallization conditions to form crystals of the molecular sieve. The method comprising:

2. The reaction mixture has the following composition expressed by molar ratio: 【Table 1A】 2. The method of claim 1, comprising:

3. The reaction mixture has the following composition, expressed in molar ratios: 【Table 1B】 2. The method of claim 1, comprising:

4. 2. The method of claim 1, wherein the alkali or alkaline earth metal (M) comprises potassium.

5. 10. The method of claim 1, wherein the crystallization conditions include a temperature of from 100° C. to 200° C. and a time of from 1 to 14 days.

6. An as-synthesized SZR framework-based molecular sieve containing 1,2,3-trimethylimidazolium cations within the pores.

7. SiO in the range of 10 to 80 2 / Al 2 O 3 7. The molecular sieve of claim 6 having a molar ratio of:

8. SiO in the range of 15 to 50 2 / Al 2 O 3 7. The molecular sieve of claim 6 having a molar ratio of:

Citation Information

Patent Citations

  • New crystalline (metalo) silicate and germanate

    JP1990258618A

  • Method for preparing small crystals of SSZ-32

    JP2013541492A

  • A process for preparing a zeolitic material having a framework structure type RTH

    WO2019154071A1